Frequency of food allergy in school‐aged children in eight European countries—The EuroPrevall‐iFAAM birth cohort. Issue 9 (19th May 2020) - Grabenhenrich, Linus; Trendelenburg, Valérie; Bellach, Johanna; Yürek, Songül; Reich, Andreas; Fiandor, Ana; Rivero, Daniela; Sigurdardottir, Sigurveig; Clausen, Michael; Papadopoulos, Nikolaos G.; Xepapadaki, Paraskevi; Sprikkelman, Aline B.; et al.
Abstract: Background: The prevalence of food allergy (FA) among European school children is poorly defined. Estimates have commonly been based on parent‐reported symptoms. We aimed to estimate the frequency of FA and sensitization against food allergens in primary school children in eight European countries. Methods: A follow‐up assessment at age 6‐10 years of a multicentre European birth cohort based was undertaken using an online parental questionnaire, clinical visits including structured interviews and skin prick tests (SPT). Children with suspected FA were scheduled for double‐blind, placebo‐controlled oral food challenges (DBPCFC). Results: A total of 6105 children participated in this school‐age follow‐up (57.8% of 10 563 recruited at birth). For 982 of 6069 children (16.2%), parents reported adverse reactions after food consumption in the online questionnaire. Of 2288 children with parental face‐to‐face interviews and/or skin prick testing, 238 (10.4%) were eligible for a DBPCFC. Sixty‐three foods were challenge‐tested in 46 children. Twenty food challenges were positive in 17 children, including seven to hazelnut and three to peanut. Another seventy‐one children were estimated to suffer FA among those who were eligible but refused DBPCFC. This yielded prevalence estimates for FA in school age between 1.4% (88 related to all 6105 participants of this follow‐up) and 3.8% (88 related to 2289 with completed eligibility assessment). Interpretation: In primary school children in eight European countries, the prevalence of FA was lower than expected even though parents of this cohort have become especially aware of allergic reactions to food. There was moderate variation between centres hampering valid regional comparisons. Abstract : Prospective observation of more than six thousand newborns estimated the frequency of food allergy, varying considerably by diagnostic approach. One in ten children had positive skin prick against common food allergens, but only few actually suffered from food allergy. This first multinational estimate of food allergy frequency challenges the widespread perception of an increase of allergic diseases. Abbreviation: SPT, skin prick test